Effect of low temperature on the retrogradation behavior of rice gels with different milling degrees. Issue 11 (3rd September 2015) - Xia, Wen; Liu, Chengmei; Luo, Shunjing; Xu, Xingfeng; Fu, Guiming
Abstract : The retrogradation properties of rice gels with different milling degrees (0, 3, 6, and 9%) stored at 4°C and −20°C were investigated. Results showed that rice gels with the same degrees of milling (DOM) stored at 4°C retrograde faster than those stored at −20°C. Moreover, higher milling degree leads to a faster retrogradation in the same temperature. Texture profile analysis demonstrated that samples showed a lower hardness but higher adhesiveness during storage at −20°C. Differential scanning calorimetry (DSC) revealed that the higher the milling degree, the higher retrogradation index (ΔHr/ΔHg) obtained at 4°C or −20°C. X‐Ray diffraction (XRD) analysis indicated that samples stored at −20°C had a lower degree of crystallinity compared with those stored at 4°C, which was also confirmed by Fourier Transform infrared spectroscopy (FTIR) analysis. Scanning electron microscopy (SEM) analysis showed that samples stored at −20°C presented a more shrinkable appearance with more pores. The results are expected to provide some theoretical guidance for retarding the retrogradation of rice in processing and preservation industry.